2023
DOI: 10.3390/biomimetics8080587
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Combined Heat and Power Economic Dispatch Problem in Different Scale Systems Using the Imperialist Competitive Harris Hawks Optimization Algorithm

Amir Nazari,
Hamdi Abdi

Abstract: The aim of electrical load dispatch (ELD) is to achieve the optimal planning of different power plants to supply the required power at the minimum operation cost. Using the combined heat and power (CHP) units in modern power systems, increases energy efficiency and, produce less environmental pollution than conventional units, by producing electricity and heat, simultaneously. Consequently, the ELD problem in the presence of CHP units becomes a very non-linear and non-convex complex problem called the combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Considering these factors is vital to prevent equipment damage, cut operating costs and enhance overall efficiency within integrated power systems. Below, we outline the contribution of this study, emphasizing the comparison with the results reported by the authors in [27,28,[32][33][34][35][36][37]:…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Considering these factors is vital to prevent equipment damage, cut operating costs and enhance overall efficiency within integrated power systems. Below, we outline the contribution of this study, emphasizing the comparison with the results reported by the authors in [27,28,[32][33][34][35][36][37]:…”
Section: Introductionmentioning
confidence: 87%
“…The third approach is presented in Equation ( 5), which utilizes a piecewise method to depict the segments that form the cost curve. This representation differs from the mathematical models published in the literature [27,28,[32][33][34][35][36][37], we propose to incorporate a binary variable that simplifies the choice of a single operating state for the CCPP. It focuses exclusively on the two non-convex states of the CCPP, which enable a transition between them, and the binary variable facilitates its selection efficiently.…”
mentioning
confidence: 99%